Building Resilience Public Organizations Through Technological Innovation In Public Services In Indonesia - Sahabuddin, Romansyah; Rahman, Fatmawati A; Wijaya, Indra Dharma (Institut Pemerintahan Dalam Negeri Kampus Sulawesi Selatan, 2025)
In today's digital era, technological innovation has become a key pillar in enhancing the effectiveness and resilience of public organizations. This study aims to analyze how technological innovation contributes to building resilient public organizations in Indonesia, particularly in the realm of public service delivery. A descriptive qualitative approach was employed, utilizing in-depth interviews and document analysis in government institutions implementing the Electronic-Based Government System (SPBE). The findings reveal that technological innovation improves service efficiency, accelerates administrative processes, and strengthens organizational capacity in responding to change and crisis. However, infrastructure disparities, low digital literacy, and resistance to change remain significant challenges that must be addressed to achieve sustainable organizational resilience.